Application of the Student Teams Achiepvement Division (STAD) Learning Model Assisted by Word Wall to Improve the Learning Outcomes of Grade IV Students of SDN 010 Rambah - Muliawati Muliawati; Safrudin Safrudin (Journal of English Language and Education, 2026)
Social studies learning in elementary schools still faces the problem of low learning outcomes and student involvement due to the dominance of teacher-centered learning. This study aims to determine the effectiveness of the application of the Student Teams Achievement Division (STAD) learning model assisted by Word Wall in improving the learning outcomes of fourth grade students of SD Negeri 010 Rambah. This study uses the Classroom Action Research approach which is carried out in two cycles with stages of planning, implementation, observation, and reflection. The research subjects amounted to 24 students. Data collection techniques include learning outcome tests, observations, and documentation, while data analysis is carried out descriptively, quantitatively, and qualitatively. The results of the study showed that the application of the Word Wall-assisted STAD model was able to improve student learning outcomes, which was characterized by an increase in average scores and classical completeness from cycle I to cycle II. In addition, student activities and the implementation of learning by teachers have also increased. The STAD model encourages individual cooperation and responsibility, while the Word Wall helps reinforce the understanding of concepts through visual media. Thus, the application of the Word Wall-assisted STAD model is effective in improving learning outcomes and creating more active and collaborative learning.